The Impact of Brexit on Foreign Direct Investment in UK - Chabbi, EL Djaida (جامعة الوادي - University of Eloued, 2023)
The aim of the current study is to investigate the impact of Brexit on Foreign Direct Investment. Brexit caused economic uncertainty, which has led to various changes in several aspects of the economy, including foreign direct investment. The latter is the issue that the study seeks to explore to what extent it is affected by Brexit. To achieve accurate findings on the impact of Brexit on foreign direct investment, study is carried out. Qualitative method is used to collect and analyze data, provides existing numerical data related to foreign direct investment inward and outward flows and the flow percentages on the gross domestic product of the country before and after Brexit. Both data visualization and comparative analysis are used to facilitate comparing and analyzing the values and percentages. Hence, the study reveals that both inflows and outflows of foreign direct investment decreased after Brexit, without ignoring the Covid-19 effect besides Brexit. Yet, inwards increased in 2021, indicating that the United Kingdom is attracting new destinations as an independent economic power. It intends to broaden its transactions and agreements abroad to encourage investors to reinvest in the United Kingdom under the new conditions. Consequently, there is a need for further research to gain comprehensive insights on this topic الهدف من الدراسة الحالية هو التحقيق في تأثير خروج بريطانيا من الاتحاد الأوروبي على الاستثمار الأجنبي المباشر. تسبب خروج بريطانيا من الاتحاد الأوروبي في حالة من عدم اليقين الاقتصادي ، مما أدى إلى تغييرات مختلفة في العديد من جوا نب الاقتصاد ، بما في ذلك الاستثمار الأجنبي المباشر. هذه الأخيرة هي القضية التي تسعى الدراسة لاستكشاف مدى تأثرها بخروج بريطانيا من الاتحاد الأوروبي. لتحقيق نتائج دقيقة حول تأثير خروج بريطانيا من الاتحاد الأوروبي على الاستثمار الأجنبي المباشر ، تم إجراء الدراسة. تُستخدم الطريقة النوعية لجمع البيانات وتحليلها ، وتوفر البيانات العددية الحالية المتعلقة بالاستثمار الأجنبي المباشر الداخلي والتدفقات الخارجية ونسب التدفق على الناتج المحلي الإجمالي للبلد قبل خروج بريطانيا من الاتحاد الأوروبي وبعده. يتم استخدام كل من تصور البيانات والتحليل المقارن لتسهيل مقارنة وتحليل القيم والنسب المئوية. ومن ثم ، كشفت الدراسة أن تدفقات الاستثمار الأجنبي المباشر إلى الداخل والخارج انخفضت بعد خروج بريطانيا من الاتحاد الأوروبي ، دون تجاهل تأثير كوفيد - 19 إلى جانب خروج بريطانيا من الاتحا د الأوروبي. ومع ذلك ، زاد الوافدون في عام 2021 ، مما يشير إلى أن المملكة المتحدة تجتذب وجهات جديدة كقوة اقتصادية مستقلة. وتعتزم توسيع معاملاتها واتفاقياتها في الخارج لتشجيع المستثمرين على إعادة الاستثمار في المملكة المتحدة في ظل الظروف الجديدة. وبالتالي ، هناك حاجة لمزيد من البحث لاكتساب رؤى شاملة حول هذا الموضوع .
Keywords: brexit, COVID-19, flows, foreign direct investment, gross domestic product.; خروج بريطانيا من الاتحاد الاوروبي ، كوفي د- 19 ، التدفقات، الاستثمار الاجنبي المباشر ، الناتج المحلي الاجمالي .